2018
DOI: 10.1002/da.22755
|View full text |Cite
|
Sign up to set email alerts
|

Individual treatment selection for patients with posttraumatic stress disorder

Abstract: Using a PAI-based algorithm has the potential to improve clinical decision making and to enhance individual patient outcomes, although further replication is necessary before such an approach can be implemented in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 58 publications
0
42
0
6
Order By: Relevance
“…Unlike traditional single-moderator studies, contemporary studies investigate the combined influence of multiple patient-attributes (e.g., demographic, diagnostic, personality features) to profile patients into subgroups that respond to treatment in similar ways. For example, multivariable prediction algorithms have been developed to identify patients who respond differentially to CBT vs. antidepressant medication (DeRubeis et al, 2014), CBT vs. interpersonal psychotherapy (Huibers et al, 2015), CBT vs. eye-movement desensitization and reprocessing (Deisenhofer et al, 2018), prolonged exposure vs. cognitive processing therapy (Keefe et al, 2018), and CBT vs. psychodynamic therapy (Cohen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike traditional single-moderator studies, contemporary studies investigate the combined influence of multiple patient-attributes (e.g., demographic, diagnostic, personality features) to profile patients into subgroups that respond to treatment in similar ways. For example, multivariable prediction algorithms have been developed to identify patients who respond differentially to CBT vs. antidepressant medication (DeRubeis et al, 2014), CBT vs. interpersonal psychotherapy (Huibers et al, 2015), CBT vs. eye-movement desensitization and reprocessing (Deisenhofer et al, 2018), prolonged exposure vs. cognitive processing therapy (Keefe et al, 2018), and CBT vs. psychodynamic therapy (Cohen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies are also leveraging the advantages of machine learning methods in order to optimize feature selection, to discover nonlinear associations and interactions between variables, and to yield prediction models that are more likely to generalise to new samples (e.g., Cohen et al, 2019;Deisenhofer et al, 2018;Delgadillo, Huey, Bennett, & McMillan, 2017;Keefe et al, 2018;Lorenzo-Luaces et al, 2017). Despite the increased sophistication of new studies, this emerging literature is still limited by old problems.…”
Section: Introductionmentioning
confidence: 99%
“…Patients reported different profiles of trauma‐related emotions that might require specifically tailored interventions depending on which emotions are most pronounced. Empirically based decision rules should guide differential indications (Deisenhofer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The higher the absolute values of the PAI, the stronger is the predicted benefit of one treatment over another. The interpretation of the PAI can be demonstrated with a recent study that used the PHQ-9 as the primary outcome and found a PAI of 2.5 [70]. This means that if patients had received their "optimal" treatment (out of the two), their PHQ-9 score at 12 weeks would have been 2.5 points lower than if they had obtained their nonoptimal treatment.…”
Section: Personalized Advantage Index (Pai)mentioning
confidence: 99%